22. Dnevi varstvoslovja, Ljubljana, 9. in 10. junij 2021: Zbornik povzetkov (University of Maribor Press, 2021)
22nd Days of Criminal Justice and Security, Ljubljana, 9th & 10th of June 2021: Book of Abstracts. Contributions of the 22nd Conference Days of Criminal Justice and Security represent professional and scientific consideration of paths and resources for provision of security in contemporary society. The book of abstracts includes abstracts of five round tables and forty-five contributions, dealing with a broad range of topics such as community policing, plural policing, private security, security and safety in local communities, various forms of violence, criminal investigation, criminology, police oversight, criminal justice and security terminology, private detective activities, the implementation of criminal sanctions, cyber security, technologies in the security provision, and other current security challenges of contemporary society.